Flexible ionic polymer binder as well as preparation method and application thereof

The flexible ionic polymer binder addresses the weaknesses of PVDF by enhancing bonding and lithium ion transmission, achieving high discharge capacity and cycle stability through a structured preparation process.

CN119242229AActive Publication Date: 2025-01-03NANKAI UNIV

Patent Information

Application Number
CN202411393804.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-08
Publication Date
2025-01-03
Estimated Expiration
2044-10-08

AI Technical Summary

Technical Problem

Current lithium-ion battery binders, such as polyvinylidene fluoride (PVDF), suffer from weak bonding forces leading to material detachment during cycling and poor lithium ion transmission, limiting high-performance battery capabilities.

Method used

A flexible ionic polymer binder with a specific chemical structure and preparation method, involving free radical polymerization, quaternization, and anion replacement, enhances bonding and lithium ion transmission by forming chemical bonds and electrostatic interactions with the positive electrode material.

Benefits of technology

The flexible ionic polymer binder improves adhesion, increases active material loading, and maintains structural integrity, resulting in high discharge specific capacity and excellent cycle stability, with a capacity retention rate of 96.59% after 800 cycles.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005073166740000021
    Figure BDA0005073166740000021
  • Figure BDA0005073166740000022
    Figure BDA0005073166740000022
  • Figure BDA0005073166740000041
    Figure BDA0005073166740000041
Patent Text Reader

Abstract

The invention provides a flexible ionic polymer binder as well as a preparation method and application thereof, and belongs to the technical field of lithium ion batteries. The invention provides a flexible ionic polymer binder, which has a chemical structure as shown in a formula I. When the binder is used for a positive electrode of a lithium ion battery, a polyacrylic acid trialkyl amino ester anionic salt chain segment provides an active site, and chemical bonds or electrostatic interaction is generated between the binder and a positive electrode active material, so that the positive electrode active material is formed. The specific type of anions improves the interaction between the binder and the positive electrode active material, and improves the capacity and cycle performance of the battery. The result of the embodiment shows that the initial specific discharge capacity of a lithium ion battery assembled by a positive pole piece prepared from the flexible ionic polymer binder provided by the invention can reach 155.2 mAh / g, the initial specific discharge capacity can still be kept at 149.9 mAh / g after 800 cycles under the current density of 0.5 C, the capacity retention rate can reach 96.59%, and the lithium ion battery has good cycle performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of lithium ion batteries, and in particular to a flexible ionic polymer binder and a preparation method and application thereof. Background Art

[0002] Lithium-ion battery is a rechargeable battery with advantages such as high energy density, long cycle life and lightweight. It has been widely used in many fields such as portable electronic devices, electric vehicles and energy storage systems. Lithium-ion batteries are mainly composed of four parts: positive electrode, negative electrode, separator and electrolyte. The positive electrode is composed of positive electrode active material, conductive agent, binder and current collector. The function of the binder is to bond the positive electrode active material and conductive agent to the current collector to form a stable positive electrode sheet. Although the amount of binder used is very small, it is an indispensable and important component in the preparation of lithium-ion battery positive electrode sheets, and plays an important role in maintaining the integrity of the electrode structure and improving the electrochemical performance of lithium-ion batteries.

[0003] At present, the most commonly used positive electrode binder for lithium-ion batteries is polyvinylidene fluoride (PVDF), which has advantages such as strong electrochemical corrosion resistance and a wide electrochemical window. However, PVDF binder has some limitations. For example, the bonding effect of PVDF generally comes from the van der Waals force between molecules. This van der Waals force is weak, which will cause the positive electrode active material and conductive agent to fall off from the current collector during the cycle process, and cannot meet the requirements of high-performance batteries; PVDF has poor lithium ion transmission capacity, which limits the transmission of lithium ions in the electrode and affects the charge and discharge performance of lithium-ion batteries at high rates.

[0004] In order to overcome the problems of PVDF binders, a lot of research has been conducted on positive electrode binders for lithium-ion batteries. For example, the prior art discloses an ionic polymer binder, in which the interaction between hexafluorophosphate and the positive electrode active material enhances the bonding between the materials and the ability to transmit lithium ions, and increases the loading amount of the positive electrode active material; however, the capacity retention rate of the battery assembled with the positive electrode sheet prepared using the binder after 800 cycles is only 90.12-92.11%; the cycle performance of the battery assembled with the positive electrode sheet prepared using the binder still cannot meet the requirements of practical applications. Summary of the invention

[0005] The purpose of the present invention is to provide a flexible ionic polymer binder and a preparation method and application thereof. The lithium ion battery assembled with the positive electrode sheet prepared by the flexible ionic polymer binder provided by the present invention has high discharge specific capacity and excellent cycle stability.

[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0007] The present invention provides a flexible ionic polymer binder having a chemical structure as shown in Formula I:

[0008]

[0009] In the formula I, R1, R6 and R7 are independently hydrogen or alkyl; R2 is alkylene or aralkylene; R3 and R4 are independently alkyl or aralkyl; R5 and R8 are independently alkyl;

[0010] X is BF4, 1 / 2[SO4], 1 / 2[CO3], CH3SO3, CF3SO3 or (CF3SO2)2N.

[0011] In the formula I, m=4-40; x+y+z=1, wherein x>0, y≥0, z≥0.

[0012] Preferably, in the formula I, R1, R6 and R7 are all hydrogen; R2 is an alkylene group; R3, R4, R5 and R8 are all alkyl groups;

[0013] X is BF4, 1 / 2[SO4], or (CF3SO2)2N;

[0014] m=4-40; x+y+z=1, wherein 0<x<0.7, 0≤y≤0.4, 0≤z≤0.4.

[0015] Preferably, the flexible ionomer binder has a chemical structure as shown below:

[0016]

[0017] The present invention also provides a method for preparing the flexible ionic polymer binder described in the above technical solution, comprising:

[0018] The first ester monomer is sequentially subjected to a first free radical polymerization, a first quaternization and a first anion replacement to obtain a flexible ionic polymer binder; the first ester monomer is dialkylamino acrylate, or a combination of one or both of polyethylene glycol acrylate and acrylate and dialkylamino acrylate;

[0019] Alternatively, the second ester monomer is subjected to a second free radical polymerization to obtain a flexible ionic polymer binder; the second ester monomer is a trialkylamino acrylate anion salt, or a combination of one or two of polyethylene glycol acrylate and acrylate and a trialkylamino acrylate anion salt; the trialkylamino acrylate anion salt is obtained by sequentially subjecting dialkylamino acrylate to a second quaternization and a second anion replacement.

[0020] Preferably, the preparation method comprises the following steps:

[0021] (1) mixing a first ester monomer, a first initiator and a first solvent to perform a first free radical polymerization reaction to obtain a first polymer solution;

[0022] (2) mixing the first polymer solution obtained in step (1) with a first alkylating agent and a second solvent to perform a first quaternization reaction to obtain a second polymer solution;

[0023] (3) The second polymer solution obtained in step (2) is mixed with the first anion salt and the third solvent to perform a first anion replacement reaction to obtain a flexible ionic polymer binder.

[0024] Preferably, the preparation method comprises the following steps:

[0025] 1) mixing dialkylamino acrylate, a second alkylating agent and a fourth solvent, and performing a second quaternization reaction to obtain a trialkylamino acrylate salt solution;

[0026] 2) mixing the acrylate trialkylamino ester salt solution obtained in step 1) with the second anion salt and the fifth solvent, and performing a second anion replacement reaction to obtain acrylate trialkylamino ester anion salt;

[0027] 3) Mixing the second ester monomer of the trialkylamino acrylate anion salt obtained in step 2), a second initiator and a sixth solvent, and performing a second free radical polymerization reaction to obtain a flexible ionic polymer binder.

[0028] The present invention also provides the use of the flexible ionic polymer binder described in the above technical solution or the flexible ionic polymer binder prepared by the preparation method described in the above technical solution in a positive electrode sheet of a lithium ion battery.

[0029] The present invention also provides a lithium-ion battery positive electrode plate, comprising a current collector and a positive electrode material coated on the surface of the current collector; the positive electrode material comprises a positive electrode active material, a binder and a conductive agent, characterized in that the binder comprises the flexible ionic polymer binder described in the above technical scheme or the flexible ionic polymer binder prepared by the preparation method described in the above technical scheme.

[0030] Preferably, the binder further comprises polyvinylidene fluoride, and the mass ratio of the flexible ionomer binder to polyvinylidene fluoride is 1:(0-5).

[0031] Preferably, the mass ratio of the positive electrode active material to the binder is (60-98):(1-20).

[0032] The present invention provides a flexible ionic polymer binder having a chemical structure as shown in Formula I. When the flexible ionic polymer binder provided by the present invention is used for the positive electrode of a lithium ion battery, the polyacrylic acid trialkylamino ester anion salt chain segment provides an active site, generates a chemical bond or electrostatic interaction between the binder and the positive electrode material, and the interaction between the binder and the positive electrode material can effectively improve the bonding between the materials, increase the positive electrode active material loading, and thus improve the capacity and cycle performance of the lithium ion battery assembled with the positive electrode sheet prepared by the binder; specific types of anions can play a role in buffering volume changes by forming chemical bonds and electrostatic interactions with the positive electrode material, thereby preventing lithium ions from causing the positive electrode to be inserted and removed. The volume change of the material leads to the destruction of the positive electrode material, ensuring the structural integrity of the positive electrode material and further improving the battery cycle performance; at the same time, specific types of anions can form specific ion pairs or complexes with lithium ions, reduce the activation energy of lithium ion migration, and make the migration of lithium ions in the electrode material smoother, further improving the battery cycle performance; by limiting the type of anions, the structure and surface properties of the electrode material can be effectively adjusted, and a lithium ion transmission channel can be constructed between the binder and the positive electrode material, which is conducive to the rapid diffusion of lithium ions inside the electrode, reducing polarization, improving lithium ion mobility, and improving the discharge specific capacity of the lithium ion battery. The data of the embodiment show that the initial discharge specific capacity of the lithium ion battery assembled by the positive electrode sheet prepared by the flexible ionic polymer binder provided by the present invention can reach 155.2mAh / g, and after 800 cycles at a current density of 0.5C, it can still maintain 149.9mAh / g, and the capacity retention rate can reach 96.59%, with good cycle performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0033] Figure 1 is the H NMR spectrum of the flexible ionic polymer binder A1 in Example 1 of the present invention;

[0034] Figure 2 is the H NMR spectrum of trimethylaminoethyl acrylate bis(trifluoromethanesulfonyl)imide salt in Example 6 of the present invention;

[0035] Figure 3 The differential scanning calorimetry curves of the flexible ionic polymer binder A1 prepared in Example 1 of the present invention and the binder B1 prepared in Comparative Example 1;

[0036] Figure 4 Cyclic voltammetry curves of lithium iron phosphate|metal lithium battery D1 at 25°C, different scan rates (0.1-0.8 mV / s), and voltage range of 2.0-4.5 V;

[0037] Figure 5Cyclic voltammetry curves of lithium iron phosphate|metal lithium battery D17 at 25°C, different scan rates (0.1-0.8mV / s), and voltage range of 2.0-4.5V;

[0038] Figure 6 The relationship between the peak current and the square root of various scan rates obtained from the cyclic voltammetry curves of lithium iron phosphate|metal lithium batteries D1 and D17 at different scan rates;

[0039] Figure 7 It is the long cycle charge and discharge curve of lithium iron phosphate|metal lithium battery D1 at 25℃, cut-off voltage of 2.5~4.2V and 0.5C rate;

[0040] Figure 8 It is the charge and discharge curve of lithium iron phosphate|lithium metal battery D1 at 25℃, cut-off voltage of 2.5~4.2V, and under the conditions of 0.05C, 0.1C, 0.2C, 0.3C and 0.5C rate conditions. DETAILED DESCRIPTION

[0041] The present invention provides a flexible ionic polymer binder having a chemical structure as shown in Formula I:

[0042]

[0043] In the formula I, R1, R6 and R7 are independently hydrogen or alkyl; R2 is alkylene or aralkylene; R3 and R4 are independently alkyl or aralkyl; R5 and R8 are independently alkyl;

[0044] X is BF4, 1 / 2[SO4], 1 / 2[CO3], CH3SO3, CF3SO3 or (CF3SO2)2N;

[0045] m=4~40;x+y+z=1, wherein x>0, y≥0, z≥0.

[0046] In the present invention, in the formula I, R1, R6 and R7 are independently hydrogen or alkyl, and the alkyl is preferably methyl; in the embodiment of the present invention, R1, R6 and R7 are preferably hydrogen.

[0047] In the present invention, R2 in the formula I is an alkylene group or an aralkylene group, preferably an alkylene group, the alkylene group is preferably an ethylene group or a propylene group, more preferably an ethylene group, and the aralkylene group is preferably a diphenyl group.

[0048] In the present invention, R3 and R4 in Formula I are independently alkyl or aralkyl, the alkyl is preferably methyl, and the aralkyl is preferably benzyl; in the embodiments of the present invention, R3 and R4 are preferably alkyl.

[0049] In the present invention, R5 and R8 in Formula I are independently alkyl groups, R5 is preferably methyl, and R8 is preferably ethyl or butyl.

[0050] In the present invention, X in the formula I is BF4, 1 / 2[SO4], 1 / 2[CO3], CH3SO3, CF3SO3 or (CF3SO2)2N, preferably BF4, 1 / 2[SO4] or (CF3SO2)2N, and more preferably (CF3SO2)2N.

[0051] In the present invention, in the formula I, m=4-40, preferably 6-25, more preferably 8-15.

[0052] In the present invention, in the formula I, x+y+z=1, the x>0, preferably 0<x<0.7, more preferably x=0.66; the y≥0, preferably 0≤y≤0.4, more preferably 0.17≤y≤0.34; the z≥0, preferably 0≤z≤0.4, more preferably 0.17≤z≤0.34.

[0053] In an embodiment of the present invention, the flexible ionomer binder is preferably

[0054]

[0055] In the present invention, by limiting the types of each group and anionic group in the structural formula and the number of each group, the interaction between the binder and the positive electrode material is further promoted, thereby ensuring the stability of the structural performance of the positive electrode material and improving the capacity and cycle performance of the lithium-ion battery assembled with the positive electrode sheet prepared by the flexible ionic polymer binder.

[0056] The interaction force between the flexible ionic polymer binder provided by the present invention and the positive electrode active material can effectively improve the adhesion between the materials and increase the loading amount of the positive electrode active material, thereby improving the capacity and cycle performance of the lithium ion battery assembled with the positive electrode sheet prepared by the binder.

[0057] The present invention also provides a method for preparing the flexible ionomer binder described in the above technical solution, comprising:

[0058] The first ester monomer is sequentially subjected to a first free radical polymerization, a first quaternization and a first anion replacement to obtain a flexible ionic polymer binder; the first ester monomer is dialkylamino acrylate, or a combination of one or both of polyethylene glycol acrylate and acrylate and dialkylamino acrylate;

[0059] Alternatively, the second ester monomer is subjected to a second free radical polymerization to obtain a flexible ionic polymer binder; the second ester monomer is a trialkylamino acrylate anion salt, or a combination of one or two of polyethylene glycol acrylate and acrylate and a trialkylamino acrylate anion salt; the trialkylamino acrylate anion salt is obtained by sequentially subjecting dialkylamino acrylate to a second quaternization and a second anion replacement.

[0060] In a technical solution of the present invention, the preparation method preferably comprises the following steps:

[0061] (1) mixing a first ester monomer, a first initiator and a first solvent to perform a first free radical polymerization reaction to obtain a first polymer solution;

[0062] (2) mixing the first polymer solution obtained in step (1) with a first alkylating agent and a second solvent to perform a first quaternization reaction to obtain a second polymer solution;

[0063] (3) The second polymer solution obtained in step (2) is mixed with the first anion salt and the third solvent to perform a first anion replacement reaction to obtain a flexible ionic polymer binder.

[0064] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0065] The present invention mixes a first ester monomer, a first initiator and a first solvent, and performs a first free radical polymerization reaction to obtain a first polymer solution.

[0066] In the present invention, the first ester monomer is preferably dialkylamino acrylate, or a combination of one or both of polyethylene glycol acrylate and acrylate with dialkylamino acrylate.

[0067] In the present invention, the dialkylamino acrylate is preferably one or more of dimethylaminoethyl acrylate, dimethylaminoethyl methacrylate, 3-(dimethylamino)propyl methacrylate and 4'-[di(4-methylphenyl)amino]biphenyl-4-yl 2-acrylate.

[0068] In the present invention, the polyethylene glycol acrylate is preferably one or both of polyethylene glycol monomethyl ether acrylate and polyethylene glycol monomethyl ether methacrylate.

[0069] In the present invention, the acrylic acid ester is preferably one or more of ethyl acrylate, ethyl methacrylate, butyl acrylate, butyl methacrylate, 2-ethylbutyl acrylate and pentyl acrylate.

[0070] In the present invention, the polyacrylic acid trialkylamino ester anion salt chain segment provides an active site, generates a chemical bond or an electrostatic interaction between the binder and the positive electrode active material, and the interaction between the binder and the positive electrode active material can effectively improve the adhesion between the materials and increase the loading amount of the positive electrode active material; the polyethylene glycol acrylate chain segment can not only improve the flexibility of the binder and soften the pole piece, but also transmit lithium ions; the hydrophobic chain segment acrylate can avoid the problem of battery capacity and cycle performance degradation caused by active material absorbing water, thereby improving the discharge specific capacity and cycle stability of the lithium ion battery; by limiting the structure and type of the reaction raw materials, the interaction between the binder and the positive electrode material is improved, and the performance of the lithium ion battery is further improved.

[0071] In the present invention, the first initiator is preferably one or more of azobisisobutyronitrile, azobiscyclohexylcarbonitrile, dimethyl azobisisobutyrate and dibenzoyl peroxide. In the present invention, the first initiator can initiate the free radical polymerization reaction of the raw materials dialkylamino acrylate, polyethylene glycol acrylate and acrylate, and the free radical polymerization reaction is fully promoted by controlling the type of initiator.

[0072] In the present invention, the first solvent is preferably one or more of dimethyl carbonate, diethyl carbonate, ethanol, ether, acetonitrile, toluene, acetone, N-methylpyrrolidone, N,N-dimethylformamide, tetrahydrofuran, dichloromethane and chloroform. In the present invention, by limiting the type of the first solvent, each reaction raw material can be fully dissolved, and the compatibility between each reaction raw material is improved, so as to promote the full progress of the free radical polymerization reaction.

[0073] In the present invention, the molar ratio of the dialkylamino acrylate, polyethylene glycol acrylate and acrylate is preferably 1:(0-1):(0-1), more preferably 1:(0.2-0.8):(0.2-0.8), and most preferably 1:(0.35-0.65):(0.35-0.65). In the present invention, by controlling the amount ratio of the reaction raw materials, the free radical polymerization reaction can proceed smoothly, further improving the performance of the binder.

[0074] In the present invention, the amount of the first initiator is preferably 0.1-2% of the mass of the first ester monomer, more preferably 0.5-1.5%, and most preferably 0.8-1.2%. In the present invention, by controlling the amount of the initiator, the free radical polymerization reaction is further promoted.

[0075] The present invention has no particular limitation on the amount of the first solvent, as long as the mass concentration of the first ester monomer is maintained at 10 to 50%, more preferably 20 to 30%.

[0076] The present invention has no special limitation on the mixing operation. The mixing operation commonly used by those skilled in the art can be used to uniformly mix the reaction raw materials.

[0077] In the present invention, the temperature of the first free radical polymerization reaction is preferably 45 to 80° C., more preferably 55 to 75° C., and most preferably 60 to 70° C.; the time of the first free radical polymerization reaction is preferably 5 to 12 hours, more preferably 6 to 10 hours, and most preferably 7 to 9 hours. In the present invention, by limiting the temperature and time of the first free radical polymerization reaction, it is ensured that the free radical polymerization reaction can proceed smoothly, and at the same time, the sufficiency of the free radical polymerization reaction is further improved.

[0078] In the present invention, the first free radical polymerization reaction is preferably carried out under an inert atmosphere; the inert atmosphere is preferably nitrogen or argon. In the present invention, the inert atmosphere can avoid interference of air on the first free radical polymerization reaction, improve product purity, and further improve the performance of the binder.

[0079] After obtaining the first polymer solution, the present invention mixes the first polymer solution, the first alkylating agent and the second solvent to perform a first quaternization reaction to obtain a second polymer solution.

[0080] In the present invention, the first alkylating agent is preferably one or more of methyl iodide, dimethyl sulfate, dimethyl carbonate, ethyl iodide, diethyl sulfate, diethyl carbonate, propyl iodide, dipropyl sulfate and dipropyl carbonate. In the present invention, the first alkylating agent can completely convert dialkylamino acrylate into trialkylamino acrylate salt; by limiting the type of the first alkylating agent, the reaction between the first alkylating agent and dialkylamino acrylate is further promoted.

[0081] In the present invention, the second solvent is preferably one or more of dimethyl carbonate, ethylene dichloride, tetrahydrofuran, dichloromethane, water, toluene and chloroform. In the present invention, by limiting the type of the second solvent, the reaction raw materials can be fully mixed, and the compatibility between the reaction raw materials is improved, so as to promote the full progress of the first quaternization reaction.

[0082] In the present invention, the molar ratio of the dialkylamino acrylate to the first alkylating agent is preferably 1:(1-1.5), more preferably 1:(1-1.2). In the present invention, by limiting the usage ratio of the dialkylamino acrylate to the first alkylating agent, the first quaternization reaction is further promoted to be fully carried out, and the performance of the binder is further improved.

[0083] The present invention has no special limitation on the amount of the second solvent, as long as the mass concentration of the first polymer and the first alkylating agent is maintained at 10-50%, more preferably 25-35%.

[0084] In the present invention, the first polymer solution, the first alkylating agent and the second solvent are preferably mixed by first dissolving the first alkylating agent in the second solvent and then dropping it into the first polymer solution. In the present invention, there is no special limitation on the dropping rate, as long as the temperature of the reaction system is maintained at 25 to 50° C. The present invention does not have any special limitation on the dropping operation, and the dropping operation well known to those skilled in the art can be used. In the present invention, by mixing by dropping, sufficient interaction between the reaction raw materials is ensured to avoid the formation of by-products.

[0085] In the present invention, the temperature of the first quaternization reaction is preferably 10 to 45° C., more preferably 10 to 30° C., and most preferably 15 to 28° C.; the time of the first quaternization reaction is preferably 1 to 12 hours, more preferably 6 to 10 hours, and most preferably 7 to 9 hours. In the present invention, by limiting the temperature and time of the first quaternization reaction, the quaternization reaction is promoted so that the raw materials can fully react.

[0086] After obtaining the second polymer solution, the present invention mixes the second polymer solution, the first anion salt and the third solvent, and performs a first anion replacement reaction to obtain a flexible ionic polymer binder.

[0087] In the present invention, the first anion salt is preferably one or more of NaBF4, KBF4, Na2SO4, Na2CO3, K2CO3, CH3SO3Na, CF3SO3Na and (CF3SO2)2NLi. In the present invention, the first anion salt provides anions in the binder; by controlling the type of anion salt, the type of anions in the binder is controlled, and the interaction between the binder and the positive electrode material is further improved.

[0088] In the present invention, the third solvent is preferably one or more of water, ethanol, N-methylpyrrolidone, N,N-dimethylformamide and dimethyl sulfoxide.

[0089] In the present invention, the molar ratio of the dialkylamino acrylate to the first anionic salt is preferably 1:(1-1.5), more preferably 1:(1-1.2). In the present invention, by limiting the amount of the first anionic salt, the first anionic salt can fully replace the anions in the trialkylamino acrylate salt, further improving the performance of the binder and the interaction between the binder and the positive electrode material.

[0090] The present invention has no special limitation on the amount of the third solvent, as long as the mass concentration of the second polymer and the first anion salt is maintained at 10-50%, more preferably 25-35%.

[0091] The present invention has no special limitation on the mixing of the second polymer solution, the first anion salt and the third solvent. The mixing operation commonly used by those skilled in the art can be used to uniformly mix the reaction raw materials.

[0092] In the present invention, the temperature of the first anion replacement reaction is preferably 10 to 45°C, more preferably 10 to 30°C, and most preferably 15 to 28°C; the time of the first anion replacement reaction is preferably 1 to 12 hours, more preferably 5 to 10 hours, and most preferably 5 to 8 hours. In the present invention, by limiting the temperature and time of the first anion replacement reaction, the occurrence of side reactions can be avoided, and the first anion replacement reaction can be fully carried out, promoting the replacement of the polymer anions in the second polymer solution by the first anion salt, and further improving the performance of the binder.

[0093] After the first anion replacement reaction is completed, the present invention preferably extracts the product obtained by the first anion replacement reaction, separates and removes the oil phase, and obtains a flexible ionic polymer binder aqueous phase dispersion.

[0094] The present invention has no special limitation on the extraction operation. An extraction operation well known to those skilled in the art can be used to separate the oil phase and the water phase of the product obtained by the first anion exchange reaction.

[0095] In the present invention, the solid content of the flexible ionic polymer binder aqueous dispersion is preferably 10 to 45%, more preferably 20 to 40%.

[0096] When the solid content of the flexible ionic polymer binder aqueous dispersion is not within the above range, the present invention preferably concentrates the flexible ionic polymer binder aqueous dispersion after extraction.

[0097] In the present invention, the concentration method is preferably vacuum distillation; the present invention has no special limitation on the operation of vacuum distillation, and the vacuum distillation operation commonly used by technicians in this field can be used to adjust the solid content of the concentrated flexible ionic polymer binder aqueous dispersion to the above range.

[0098] After obtaining the flexible ionic polymer binder aqueous phase dispersion, the present invention preferably sequentially cools, filters and dries the flexible ionic polymer binder aqueous phase dispersion.

[0099] The present invention has no particular limitation on the cooling operation, and the flexible ionic polymer binder aqueous dispersion can be cooled to 5-10° C. In the present invention, the flexible ionic polymer binder can be precipitated by the cooling operation.

[0100] The present invention has no special limitation on the filtering operation, and any filtering operation well known to those skilled in the art may be used.

[0101] In the present invention, the drying method is preferably vacuum drying; the drying temperature is preferably 30-80°C, more preferably 40-70°C, most preferably 50-60°C; the drying time is preferably 1-24h, more preferably 5-20h, most preferably 12-15h.

[0102] In another technical solution of the present invention, the preparation method preferably comprises the following steps:

[0103] 1) mixing dialkylamino acrylate, a second alkylating agent and a fourth solvent, and performing a second quaternization reaction to obtain a trialkylamino acrylate salt solution;

[0104] 2) mixing the acrylate trialkylamino ester salt solution obtained in step 1) with the second anion salt and the fifth solvent, and performing a second anion replacement reaction to obtain acrylate trialkylamino ester anion salt;

[0105] 3) Mixing the second ester monomer of the trialkylamino acrylate anion salt obtained in step 2), a second initiator and a sixth solvent, and performing a second free radical polymerization reaction to obtain a flexible ionic polymer binder.

[0106] The present invention has no particular limitation on the sources of the raw materials, and commercially available products known to those skilled in the art may be used.

[0107] The invention mixes dialkylamino acrylate, a second alkylating agent and a fourth solvent, and performs a second quaternization reaction to obtain a trialkylamino acrylate salt solution.

[0108] In the present invention, the structure and type of the dialkylamino acrylate are preferably the same as the structure and type of the aforementioned dialkylamino acrylate; the type of the second alkylating agent is preferably the same as the type of the aforementioned first alkylating agent; the type of the fourth solvent is preferably the same as the type of the aforementioned second solvent, which will not be repeated here.

[0109] In the present invention, the molar ratio of the dialkylamino acrylate to the second alkylating agent is preferably 1:(1-1.5), more preferably 1:(1-1.2). In the present invention, by limiting the usage ratio of the dialkylamino acrylate to the second alkylating agent, the second quaternization reaction is promoted to be fully carried out, and the performance of the binder is further improved.

[0110] The present invention has no particular limitation on the amount of the fourth solvent, as long as the mass concentration of the dialkylamino acrylate and the second alkylating agent is maintained at 10-50%, more preferably 40-50%.

[0111] The present invention has no special limitation on the mixing operation of the dialkylamino acrylate, the second alkylating agent and the fourth solvent. The mixing operation commonly used by those skilled in the art can be used to uniformly mix the reaction raw materials.

[0112] In the present invention, the temperature and time of the second quaternization reaction are preferably the same as those of the first quaternization reaction, which will not be described in detail herein.

[0113] After obtaining the trialkylamino acrylate salt solution, the present invention mixes the trialkylamino acrylate salt solution with the second anion salt and the fifth solvent to perform a second anion replacement reaction to obtain the trialkylamino acrylate anion salt.

[0114] In the present invention, the type of the second anion salt is preferably the same as the type of the first anion salt; the type of the fifth solvent is preferably the same as the type of the third solvent, which will not be described in detail herein.

[0115] In the present invention, the molar ratio of the dialkylamino acrylate to the second anionic salt is preferably 1:(1-1.5), more preferably 1:(1-1.2). In the present invention, by limiting the amount of the second anionic salt, the second anionic salt can fully replace the anions in the trialkylamino acrylate salt, further improving the performance of the binder and the interaction between the binder and the positive electrode active material.

[0116] The present invention has no special limitation on the amount of the fifth solvent, as long as the mass concentration of the trialkylamino acrylate salt and the second anion salt is maintained at 10-50%, more preferably 40-50%.

[0117] In the present invention, the mixture of the trialkylamino acrylate salt solution, the second anion salt and the fifth solvent is preferably mixed by dropping the second anion salt and the fifth solvent into the trialkylamino acrylate salt solution. In the present invention, there is no particular limitation on the dropping rate, as long as the temperature of the reaction system is maintained at 25 to 50° C. The present invention has no particular limitation on the dropping operation, and the dropping operation well known to those skilled in the art can be used.

[0118] In the present invention, the temperature and time of the second anion replacement reaction are preferably the same as the temperature and time of the first anion replacement reaction, which will not be repeated here. In the present invention, the trialkylamino acrylate anion salt is obtained by the second anion replacement reaction. The quaternary ammonium salt cations and anions in the trialkylamino acrylate anion salt can enhance the bonding between the positive electrode active materials through the electrostatic interaction with the active materials in the positive electrode plate. On the other hand, the anions in the trialkylamino acrylate anion salt can promote the transmission of lithium ions, further improving the battery performance.

[0119] After the second anion replacement reaction is completed, the product of the second anion replacement reaction is preferably precipitated, filtered and dried in sequence to obtain a trialkylamino acrylate anion salt.

[0120] In the present invention, the precipitation is preferably carried out by adding a precipitant to the product of the second anion replacement reaction; the precipitant is preferably one or more of dichloromethane, dichloroethane, ethanol, ether and water. In the present invention, the precipitation of the trialkylamino acrylate anion salt is achieved by adding a precipitant, and the precipitation of the trialkylamino acrylate anion salt is further promoted by controlling the type of the precipitant.

[0121] The present invention has no special limitation on the amount of the precipitant, as long as it can precipitate the trialkylamino acrylate anion salt.

[0122] The present invention has no particular limitation on the filtering operation, and any filtering operation well known to those skilled in the art may be used.

[0123] In the present invention, the drying method is preferably vacuum drying; the drying temperature is preferably 20-40°C, more preferably 25-35°C, most preferably 28-30°C; the drying time is preferably 6-24h, more preferably 10-20h, most preferably 12-15h.

[0124] After obtaining the trialkylamino acrylate anion salt, the present invention mixes the second ester monomer including the trialkylamino acrylate anion salt, a second initiator and a sixth solvent to carry out a second free radical polymerization reaction to obtain a flexible ionic polymer binder.

[0125] In the present invention, the second ester monomer is preferably trialkylamino acrylate anion salt, or a combination of one or both of polyethylene glycol acrylate and acrylate and trialkylamino acrylate anion salt.

[0126] In the present invention, the second initiator is preferably one or more of ammonium persulfate, potassium persulfate, sodium persulfate, azobisisobutylamidine hydrochloride and azobisisobutylimidazoline hydrochloride, more preferably one or more of ammonium persulfate, potassium persulfate and sodium persulfate. In the present invention, the second initiator can initiate a second free radical polymerization reaction, and the second free radical polymerization reaction can be further promoted by controlling the type of initiator.

[0127] In the present invention, the sixth solvent is preferably one or more of water, ethanol, methanol and acetonitrile, more preferably water or ethanol. In the present invention, the sixth solvent can dissolve the second ester monomer, while improving the compatibility of the raw materials, so that the reaction raw materials can be fully contacted, and promote the second free radical polymerization reaction.

[0128] In the present invention, the molar ratio of the trialkylamino acrylate anion salt, polyethylene glycol acrylate and acrylate is preferably 1:(0-1):(0-1), more preferably 1:(0.2-0.8):(0.2-0.8), and most preferably 1:(0.35-0.65):(0.35-0.65). In the present invention, by controlling the amount ratio of each reaction raw material, the free radical polymerization reaction can proceed smoothly, and the performance of the binder is further improved.

[0129] In the present invention, the mass of the second initiator is preferably 0.1-2% of the mass of the second ester monomer, more preferably 0.5-1.5%, and most preferably 0.8-1.2%. In the present invention, the free radical polymerization reaction is further promoted by controlling the amount of the initiator.

[0130] The present invention has no particular limitation on the amount of the sixth solvent, as long as the mass concentration of the second ester monomer is maintained at 10 to 50%, more preferably 20 to 30%. In the present invention, by controlling the concentration of the reaction raw materials, it is ensured that the reaction raw materials can be fully contacted, further promoting the full progress of the free radical polymerization reaction.

[0131] The present invention has no special limitation on the mixing operation of the second ester monomer, the second initiator and the sixth solvent. The mixing operation commonly used by those skilled in the art can be used to uniformly mix the reaction raw materials.

[0132] In the present invention, the temperature and time of the second free radical polymerization reaction are preferably the same as the temperature and time of the first free radical polymerization reaction, which will not be described in detail herein.

[0133] After the second free radical polymerization reaction is completed, the present invention preferably extracts the product obtained by the second free radical polymerization reaction, separates and removes the oil phase, and obtains a flexible ionic polymer binder aqueous phase dispersion.

[0134] The present invention has no particular limitation on the extraction operation. An extraction operation well known to those skilled in the art may be used to separate the oil phase and the water phase of the product obtained by the second free radical polymerization reaction.

[0135] In the present invention, the solid content of the flexible ionic polymer binder aqueous dispersion is preferably 10 to 45%, more preferably 20 to 40%.

[0136] When the solid content of the flexible ionic polymer binder aqueous dispersion is not within the above range, the present invention preferably concentrates the flexible ionic polymer binder aqueous dispersion after extraction.

[0137] In the present invention, the concentration method is preferably vacuum distillation; the present invention has no special limitation on the operation of vacuum distillation, and the vacuum distillation operation commonly used by technicians in this field can be used to adjust the solid content of the concentrated flexible ionic polymer binder aqueous dispersion to the above range.

[0138] After obtaining the flexible ionic polymer binder aqueous phase dispersion, the present invention preferably sequentially cools, filters and dries the flexible ionic polymer binder aqueous phase dispersion.

[0139] The present invention has no particular limitation on the cooling operation, and the flexible ionic polymer binder aqueous dispersion can be cooled to 5-10° C. In the present invention, the flexible ionic polymer binder can be precipitated by cooling.

[0140] The present invention has no particular limitation on the filtering operation, and any filtering operation well known to those skilled in the art may be used.

[0141] In the present invention, the drying method is preferably vacuum drying; the drying temperature is preferably 30-80°C, more preferably 40-70°C, most preferably 50-60°C; the drying time is preferably 1-24h, more preferably 5-20h, most preferably 12-15h.

[0142] The preparation method of the flexible ionic polymer binder provided by the present invention ensures that the raw materials react fully and avoids the occurrence of side reactions by controlling the dosage of the reaction raw materials and the process parameters of each chemical reaction, thereby further improving the performance of the flexible ionic polymer binder.

[0143] The present invention also provides the use of the above-mentioned flexible ionic polymer binder or the flexible ionic polymer binder prepared by the preparation method described in the above technical solution in a positive electrode sheet of a lithium ion battery.

[0144] The present invention also provides a lithium-ion battery positive electrode plate, comprising a current collector and a positive electrode material coated on the surface of the current collector; the positive electrode material comprises a positive electrode active material, a binder and a conductive agent, and the binder comprises the flexible ionic polymer binder described in the above technical scheme or the flexible ionic polymer binder prepared by the preparation method described in the above technical scheme.

[0145] In the present invention, the binder preferably further comprises polyvinylidene fluoride, and the mass ratio of the flexible ionic polymer binder to polyvinylidene fluoride is preferably 1:(0-5), more preferably 1:(0-1). In the present invention, by limiting the composition of the binder, the interaction between the binder and the positive electrode material is further improved.

[0146] In the present invention, the mass ratio of the positive electrode active material, the binder and the conductive agent is preferably (60-98): (1-20): (1-20), more preferably (80-98): (1-10): (1-10), and most preferably (88-96): (2-6): (2-6). The present invention further improves the electrochemical performance of the lithium ion battery by controlling the mass ratio of the positive electrode active material, the binder and the conductive agent.

[0147] In the present invention, the positive electrode active material is preferably one of lithium iron phosphate, lithium cobalt oxide, lithium manganate, ternary nickel cobalt manganese 811, ternary nickel cobalt manganese 523, ternary nickel cobalt aluminum 811, ternary nickel cobalt manganese 622, ternary nickel cobalt manganese 613 and lithium titanate; the conductive agent is preferably one or more of superconducting carbon black, carbon nanotubes, acetylene black and ketjen black. The present invention can make the lithium ion battery have good electrochemical performance by using the above-mentioned types of positive electrode active materials and conductive agents.

[0148] The present invention limits the composition of the positive electrode sheet of the lithium ion battery to ensure that the binder and the positive electrode active material can fully contact and fit each other, give full play to the bonding effect of the binder, and further improve the discharge specific capacity and cycle performance of the lithium ion battery.

[0149] The present invention has no special limitation on the preparation method of the positive electrode sheet of the lithium ion battery, and the positive electrode sheet can be prepared by a coating method well known to those skilled in the art.

[0150] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0151] Example 1

[0152] A flexible ionomer binder A1 has the chemical structure shown below:

[0153]

[0154] The molecular weight of the flexible ionic polymer is 5.81×10 4 Da;

[0155] The preparation method of the flexible ionomer binder comprises the following steps:

[0156] (1) Under a nitrogen atmosphere, a first ester monomer consisting of 1100 g of dimethylaminoethyl acrylate and 1901 g of polyethylene glycol acrylate, 30 g of azobisisobutyronitrile and 7990 g of dimethyl carbonate are mixed in a reaction kettle, and a first free radical polymerization reaction is carried out at 70° C. for 8 hours to obtain a first polymer solution; wherein the molar ratio of dimethylaminoethyl acrylate to polyethylene glycol acrylate is 1:0.5, the mass of azobisisobutyronitrile is 1% of the mass of the first ester monomer, and the mass concentration of the first ester monomer is 27.3%;

[0157] (2) dissolving 1200 g of methyl iodide in 1700 g of dimethyl carbonate to obtain a mixed solution, then dropwise adding the mixed solution to the first polymer solution obtained in step (1), mixing, and performing a first quaternization reaction at 25° C. for 8 h to obtain a second polymer solution; wherein the molar ratio of dimethylaminoethyl acrylate to methyl iodide is 1:1.1, and the mass concentration of the first polymer and methyl iodide is 30%;

[0158] (3) adding the second polymer solution obtained in step (2) dropwise to a solution consisting of 2645 g of lithium bis(trifluoromethylsulfonyl)imide and 6171 g of water, wherein the concentration of lithium bis(trifluoromethylsulfonyl)imide in the solution consisting of lithium bis(trifluoromethylsulfonyl)imide and water is 30 wt %, and performing a first anion replacement reaction at 25° C. for 6 h to obtain an oil-water two-phase mixture of a flexible ionic polymer binder; wherein the molar ratio of dimethylaminoethyl acrylate to lithium bis(trifluoromethylsulfonyl)imide is 1:1.2;

[0159] After the first anion replacement reaction is completed, the oil-water two-phase mixture of the flexible ionic polymer binder is extracted and separated, and the oil phase is removed to obtain an aqueous dispersion of the flexible ionic polymer binder; the aqueous dispersion is concentrated to a solid content of 35wt% by reduced pressure distillation, and then cooled to 5°C, and the flexible ionic polymer binder is precipitated; the precipitate is filtered to obtain a solid product, and the product is vacuum dried at 60°C for 12 hours to obtain 4095g of flexible ionic polymer binder A1.

[0160] The flexible ionic polymer binder A1 was characterized by using a nuclear magnetic resonance instrument, and the obtained nuclear magnetic hydrogen spectrum is as follows Figure 1 As shown. Figure 1 It can be seen that the hydrogen absorption signals of the two structural units corresponding to A1 prove that Example 1 indeed obtains the compound with the shown chemical structure.

[0161] Example 2

[0162] A flexible ionomer binder A2 has the chemical structure shown below:

[0163]

[0164] The molecular weight of the flexible ionic polymer binder is 5.51×10 4 Da.

[0165] The preparation method of the flexible ionomer binder comprises the following steps:

[0166] (1) Under a nitrogen atmosphere, a first ester monomer consisting of 1150 g of dimethylaminoethyl acrylate and 1988 g of polyethylene glycol acrylate, 31.4 g of azobisisobutyronitrile and 8860 g of dimethyl carbonate were mixed in a reaction kettle, and a first free radical polymerization reaction was carried out at 70° C. for 8 h to obtain a first polymer solution; wherein the molar ratio of dimethylaminoethyl acrylate to polyethylene glycol acrylate was 1:0.5, the mass of azobisisobutyronitrile was 1% of the mass of the first ester monomer, and the mass concentration of the first ester monomer was 26.15%;

[0167] (2) dissolving 1254 g of methyl iodide in 1850 g of dimethyl carbonate, and then adding the solution dropwise to the first polymer solution obtained in step (1), mixing the solution, and performing a first quaternization reaction at 25° C. for 8 h to obtain a second polymer solution; wherein the molar ratio of dimethylaminoethyl acrylate to methyl iodide is 1:1.1, and the mass concentration of the first polymer and methyl iodide is 29.1%;

[0168] (3) adding the second polymer solution obtained in step (2) dropwise to a solution consisting of 1062 g of sodium tetrafluoroborate and 2478 g of water, wherein the concentration of sodium tetrafluoroborate in the solution consisting of sodium tetrafluoroborate and water is 30 wt %, and performing a first anion replacement reaction at 25° C. for 6 h to obtain an oil-water two-phase mixture of a flexible ionic polymer binder; wherein the molar ratio of dimethylaminoethyl acrylate to sodium tetrafluoroborate is 1:1.2;

[0169] After the first anion replacement reaction is completed, the oil-water two-phase mixture of the flexible ionic polymer binder is extracted and separated, and the oil phase is removed to obtain an aqueous dispersion of the flexible ionic polymer binder; the aqueous dispersion is concentrated to a solid content of 35wt% by reduced pressure distillation, and then cooled to 5°C, and the ionic polymer binder is precipitated; the precipitate is filtered to obtain a solid product, and the product is vacuum dried at 60°C for 12 hours to obtain 3997g of flexible ionic polymer binder A2.

[0170] Example 3

[0171] A flexible ionomer binder A3 has the chemical structure shown below:

[0172]

[0173] The molecular weight of the flexible ionic polymer is 5.50×10 4 Da

[0174] The preparation method of the flexible ionomer binder comprises the following steps:

[0175] (1) Under a nitrogen atmosphere, a first ester monomer consisting of 960 g of dimethylaminoethyl acrylate and 1659 g of polyethylene glycol acrylate, 26.2 g of azobisisobutyronitrile and 8262 g of dimethyl carbonate were mixed in a reaction kettle, and a first free radical polymerization reaction was carried out at 70° C. for 8 h to obtain a first polymer solution; wherein the molar ratio of dimethylaminoethyl acrylate to polyethylene glycol acrylate was 1:0.5, the mass of azobisisobutyronitrile was 1% of the mass of the first ester monomer, and the mass concentration of the first ester monomer was 24.07%;

[0176] (2) dissolving 1014 g of dimethyl sulfate in 1720 g of dimethyl carbonate, and then adding the solution dropwise to the first polymer solution obtained in step (1), mixing the solution, and performing a first quaternization reaction at 25° C. for 8 h to obtain a second polymer solution; wherein the molar ratio of dimethylaminoethyl acrylate to methyl iodide is 1:1.2, and the mass concentration of the first polymer and dimethyl sulfate is 26.7%;

[0177] (3) adding the second polymer solution obtained in step (2) dropwise to a solution consisting of 1142 g of sodium sulfate and 2665 g of water, wherein the concentration of sodium sulfate in the solution consisting of sodium sulfate and water is 30 wt %, and performing a first anion replacement reaction at 25° C. for 6 h to obtain an oil-water two-phase mixture of a flexible ionic polymer binder; wherein the molar ratio of dimethylaminoethyl acrylate to sodium sulfate is 1:1.2;

[0178] After the first anion replacement reaction is completed, the oil-water two-phase mixture of the flexible ionic polymer binder is extracted and separated, and the oil phase is removed to obtain an aqueous dispersion of the flexible ionic polymer binder; the aqueous dispersion is concentrated to a solid content of 35 wt% by vacuum distillation, and then cooled to 5°C, and the ionic polymer binder is precipitated; the precipitate is filtered to obtain a solid product, and the product is vacuum dried at 60°C for 12 hours to obtain 2907 g of flexible ionic polymer binder A3.

[0179] Example 4

[0180] A flexible ionomer binder A4 has the chemical structure shown below:

[0181]

[0182] The molecular weight of the flexible ionic polymer is 4.36×10 4Da

[0183] The preparation method of the flexible ionomer binder comprises the following steps:

[0184] (1) Under a nitrogen atmosphere, a first ester monomer consisting of 1328 g of dimethylaminoethyl acrylate, 1148 g of polyethylene glycol acrylate and 297 g of butyl acrylate, 27.7 g of azobisisobutyronitrile and 7220 g of dimethyl carbonate were mixed in a reaction kettle, and a first free radical polymerization reaction was carried out at 70° C. for 8 hours to obtain a first polymer solution; wherein the molar ratio of dimethylaminoethyl acrylate, polyethylene glycol acrylate and butyl acrylate was 1:0.25:0.25, the mass of azobisisobutyronitrile was 1% of the mass of the first ester monomer, and the mass concentration of the first ester monomer was 27.74%;

[0185] (2) dissolving 1448 g of methyl iodide in 2050 g of dimethyl carbonate, and then adding the solution dropwise to the first polymer solution obtained in step (1), mixing the solution, and performing a first quaternization reaction at 25° C. for 8 h to obtain a second polymer solution; wherein the molar ratio of dimethylaminoethyl acrylate to methyl iodide is 1:1.1, and the mass concentration of the first polymer and methyl iodide is 31.3%;

[0186] (3) adding the second polymer solution obtained in step (2) dropwise to a solution consisting of 2929 g of lithium bis(trifluoromethylsulfonyl)imide and 6834 g of water, wherein the concentration of lithium bis(trifluoromethylsulfonyl)imide in the solution consisting of lithium bis(trifluoromethylsulfonyl)imide and water is 30 wt %, and performing a first anion replacement reaction at 25° C. for 6 h to obtain an oil-water two-phase mixture of a flexible ionic polymer binder; wherein the molar ratio of dimethylaminoethyl acrylate to lithium bis(trifluoromethylsulfonyl)imide is 1:1.1;

[0187] After the first anion replacement reaction is completed, the oil-water two-phase mixture of the flexible ionic polymer binder is extracted and separated, and the oil phase is removed to obtain an aqueous dispersion of the flexible ionic polymer binder; the aqueous dispersion is concentrated to a solid content of 35wt% by vacuum distillation, and then cooled to 5°C, and the ionic polymer binder is precipitated; the precipitate is filtered to obtain a solid product, and the product is vacuum dried at 60°C for 12 hours to obtain 4095g of flexible ionic polymer binder A4.

[0188] Example 5

[0189] A flexible ionomer binder A5 has the chemical structure shown below:

[0190]

[0191] The molecular weight of the flexible ionic polymer is 4.01×104 Da;

[0192] The preparation method of the flexible ionomer binder comprises the following steps:

[0193] (1) Under a nitrogen atmosphere, a first ester monomer consisting of 1328 g of dimethylaminoethyl acrylate and 659 g of butyl methacrylate, 19.9 g of azobisisobutyronitrile and 4680 g of dimethyl carbonate were mixed in a reaction kettle, and a first free radical polymerization reaction was carried out at 70° C. for 8 h to obtain a first polymer solution; wherein the molar ratio of dimethylaminoethyl acrylate to butyl acrylate was 1:0.5, the mass of azobisisobutyronitrile was 1% of the mass of the first ester monomer, and the mass concentration of the first ester monomer in the reaction raw material mixture was 29.8%;

[0194] (2) dissolving 1448 g of methyl iodide in 1880 g of dimethyl carbonate, and then adding the solution dropwise to the first polymer solution obtained in step (1), mixing the solution, and performing a first quaternization reaction at 25° C. for 8 h to obtain a second polymer solution; wherein the molar ratio of dimethylaminoethyl acrylate to methyl iodide is 1:1.1, and the mass concentration of the first polymer and methyl iodide is 34.4%;

[0195] (3) adding the second polymer solution obtained in step (2) dropwise to a solution consisting of 3195 g of lithium bis(trifluoromethylsulfonyl)imide and 7455 g of water, wherein the concentration of lithium bis(trifluoromethylsulfonyl)imide in the solution consisting of lithium bis(trifluoromethylsulfonyl)imide and water is 30 wt %, and performing a first anion replacement reaction at 25° C. for 6 h to obtain an oil-water two-phase mixture of a flexible ionic polymer binder; wherein the molar ratio of dimethylaminoethyl acrylate to lithium bis(trifluoromethylsulfonyl)imide is 1:1.2;

[0196] After the first anion replacement reaction is completed, the oil-water two-phase mixture of the flexible ionic polymer binder is extracted and separated, and the oil phase is removed to obtain an aqueous dispersion of the flexible ionic polymer binder; the aqueous dispersion is concentrated to a solid content of 35 wt% by vacuum distillation, and then cooled to 5°C, and the ionic polymer binder is precipitated; the precipitate is filtered to obtain a solid product, and the product is vacuum dried at 60°C for 12 hours to obtain 3070 g of flexible ionic polymer binder A5.

[0197] Example 6

[0198] A flexible ionomer binder A6 has the chemical structure shown below:

[0199]

[0200] The molecular weight of the flexible ionic polymer is 5.89×104 Da;

[0201] The preparation method of the flexible ionomer binder comprises the following steps:

[0202] 1) 197 g of methyl iodide was added dropwise to a solution of 200 g of dimethylaminoethyl acrylate and 467 g of water, and a second quaternization reaction was carried out at 25° C. for 6 h to obtain a trialkylaminoacrylate salt solution; wherein the molar ratio of dimethylaminoethyl acrylate to methyl iodide was 1:1, and the mass concentration of dimethylaminoethyl acrylate and methyl iodide was 46%;

[0203] 2) adding a solution consisting of 481 g of lithium bis(trifluoromethylsulfonylimide) and 591 g of water dropwise to the solution of trialkylamino acrylate salt obtained in step 1) and mixing, wherein the concentration of lithium bis(trifluoromethylsulfonylimide in the solution consisting of lithium bis(trifluoromethylsulfonylimide) and water is 45 wt %, and performing a second anion replacement reaction at 25° C. for 8 h to obtain trialkylamino acrylate anion salt; wherein the molar ratio of dimethylaminoethyl acrylate to lithium bis(trifluoromethylsulfonylimide) is 1:1.2, and the mass concentration of trialkylamino acrylate salt and lithium bis(trifluoromethylsulfonylimide) is 45.4%;

[0204] After the second anion replacement reaction was completed, the mixture was added to a precipitant of 19000 g of dichloroethane to precipitate, and a light yellow precipitate was precipitated. The precipitate was filtered and vacuum dried at 30° C. for 12 h to obtain 600 g of trimethylaminoethyl acrylate bistrifluoromethylsulfonyl imide salt;

[0205] The chemical structure of the trimethylaminoethyl acrylate bis(trifluoromethylsulfonyl)imide salt is as follows:

[0206]

[0207] 3) Under a nitrogen atmosphere, 600 g of the first ester monomer consisting of trimethylaminoethyl acrylate bistrifluoromethylsulfonyl imide salt obtained in step 2) and 339 g of polyethylene glycol acrylate, 9.4 g of potassium persulfate and 3000 g of water were mixed in a reaction kettle, and a second free radical polymerization reaction was carried out at 70° C. for 8 hours to obtain an oil-water two-phase mixture of a flexible ionic polymer binder; wherein the molar ratio of trimethylaminoethyl acrylate bistrifluoromethylsulfonyl imide salt and polyethylene glycol acrylate was 1:0.5, the mass of potassium persulfate was 1% of the sum of the mass of the second ester monomers, and the total mass concentration of the second ester monomers was 23.8%;

[0208] After the second free radical polymerization reaction is completed, the oil-water two-phase mixture of the flexible ionic polymer binder is extracted and separated, and the oil phase is removed to obtain an aqueous dispersion of the flexible ionic polymer binder; the aqueous dispersion is concentrated to a solid content of 35wt% by reduced pressure distillation, and then cooled to 5°C, and the ionic polymer binder is precipitated; the precipitate is filtered to obtain a solid product, and the product is vacuum dried at 60°C for 12 hours to obtain 909g of flexible ionic polymer binder A6.

[0209] The intermediate product of Example 2, trimethylaminoethyl acrylate bis(trifluoromethylsulfonyl)imide salt, was detected by nuclear magnetic resonance, and the obtained nuclear magnetic hydrogen spectrum was as follows: Figure 2 As shown. Figure 2 It can be seen that Example 6 indeed synthesized the intermediate product trimethylaminoethyl acrylate bistrifluoromethylsulfonyl imide salt.

[0210] Example 7

[0211] A flexible ionomer binder A7 has the chemical structure shown below:

[0212]

[0213] The molecular weight of the flexible ionic polymer is 4.99×10 4 Da;

[0214] The preparation method of the flexible ionomer binder comprises the following steps:

[0215] Under a nitrogen atmosphere, a second ester monomer consisting of 1222 g of the trialkylamino acrylate anion salt obtained in Example 6 and 524 g of polyethylene glycol acrylate was mixed with 17.5 g of potassium persulfate and 6240 g of water in a reactor, and a second free radical polymerization reaction was carried out at 70° C. for 8 h to obtain an oil-water two-phase mixture of a flexible ionic polymer binder; wherein the molar ratio of trimethylaminoethyl acrylate bistrifluoromethylsulfonyl imide salt and polyethylene glycol acrylate was 1:0.38, the mass of potassium persulfate was 1% of the mass of the second ester monomer, and the mass concentration of the second ester monomer was 27.98%;

[0216] After the second free radical polymerization reaction is completed, the oil-water two-phase mixture of the flexible ionic polymer binder is extracted and separated, and the oil phase is removed to obtain an aqueous dispersion of the flexible ionic polymer binder; the aqueous dispersion is concentrated to a solid content of 35wt% by vacuum distillation, and then cooled to 5°C, and the ionic polymer binder is precipitated; the precipitate is filtered to obtain a solid product, and the product is vacuum dried at 60°C for 12 hours to obtain 1595g of flexible ionic polymer binder A7.

[0217] Example 8

[0218] A flexible ionomer binder A8 has the chemical structure shown below:

[0219]

[0220] The molecular weight of the flexible ionic polymer is 2.91×10 4 Da;

[0221] The preparation method of the flexible ionomer binder comprises the following steps:

[0222] Under a nitrogen atmosphere, 1380 g of the trialkylamino acrylate anion salt obtained in Example 6, 13.8 g of potassium persulfate and 5500 g of water were mixed in a reactor, and a second free radical polymerization reaction was carried out at 70° C. for 8 hours to obtain a flexible ionic polymer binder aqueous phase dispersion; wherein the mass of potassium persulfate was 1% of the mass of trimethylaminoethyl acrylate bistrifluoromethylsulfonyl imide salt, and the mass concentration of trimethylaminoethyl acrylate bistrifluoromethylsulfonyl imide salt was 20%;

[0223] After the second free radical polymerization reaction is completed, the aqueous dispersion is concentrated to a solid content of 35 wt% by reduced pressure distillation and then cooled to 5°C, and the ionic polymer binder is precipitated; the precipitate is filtered to obtain a solid product, and the product is vacuum dried at 60°C for 12 hours to obtain 1355 g of flexible ionic polymer binder A8.

[0224] Comparative Example 1

[0225] 1000 g of dried polyvinylidene fluoride PVDF (HSV900) and 9000 g of N-methylpyrrolidone were mixed in a reaction kettle and stirred at 25° C. for 12 h to prepare a PVDF binder solution, which was recorded as B1.

[0226] Comparative Example 2

[0227] Chinese patent CN118240508A discloses an ionic polymer binder and its preparation method and application. The ionic polymer binder prepared in Example 1 of patent CN118240508A is denoted as B2;

[0228] Comparative Example 3

[0229] 400 g of sodium carboxymethyl cellulose powder (MAC500LC, Shenzhen Kejing), 1712 g of styrene-butadiene rubber latex (Shenzhen Kejing, S2919, the mass fraction of the polymer is 35%) and 9000 g of pure water (resistivity greater than 0.1 MΩ·cm) were mixed in a reactor and stirred at 25° C. for 12 h to obtain a binder solution, which was recorded as B3.

[0230] Application Examples 1 to 8

[0231] A1 to A8 prepared in Examples 1 to 8 are respectively used as binders in step ① of the following preparation method, and the prepared lithium ion battery positive electrode sheets are denoted as C1 to C8 in sequence;

[0232] A method for preparing a positive electrode sheet of a lithium-ion battery comprises the following steps:

[0233] ① Mix 10g of binder with 90g of N-methylpyrrolidone at 25°C for 10h to obtain a binder solution with a viscosity of 103mPa·s:

[0234] ② 180 g of lithium iron phosphate and 10 g of superconducting carbon black were ball-milled at a speed of 1032 rpm for 2 h to obtain a mixed powder; wherein the mass ratio of lithium iron phosphate, superconducting carbon black and flexible ionic polymer binder was 90:5:5;

[0235] ③ Add 100 g of the binder solution obtained in step ① to the mixed powder obtained in step ②, ball mill at a speed of 1032 rpm for 4 h, then add 70 g of N-methylpyrrolidone and continue ball milling for 4 h to obtain a positive electrode slurry;

[0236] ④ The positive electrode slurry obtained in step ③ is coated on aluminum foil, first dried at 80°C under normal pressure for 12 hours, then dried at 80°C under vacuum for 12 hours, and then rolled and cut into pieces in sequence to prepare lithium iron phosphate positive electrode sheets C1 to C8.

[0237] Application Examples 9 to 16

[0238] The only difference between Application Examples 9 to 16 and Application Examples 1 to 8 is that the binder in step ① is a composition of A1 to A8 prepared in Examples 1 to 8 and polyvinylidene fluoride PVDF (HSV900) in a mass ratio of 1:1, and the rest is the same as Application Examples 1 to 8. The prepared lithium-ion battery positive electrode sheets are respectively denoted as C9 to C16.

[0239] Comparative application example 1

[0240] The PVDF binder solution B1 prepared in Comparative Example 1 was used to prepare a lithium iron phosphate positive electrode sheet for a lithium-ion battery. The difference from Application Example 1 was that B1 prepared in Comparative Example 1 was used as the binder solution, and the remaining steps were the same as those in Application Example 1 to prepare a lithium iron phosphate positive electrode sheet, which was recorded as C17.

[0241] Comparative Application Example 2

[0242] The lithium iron phosphate positive electrode sheet prepared in Application Example 1 of Patent CN118240508A (lithium iron phosphate positive electrode sheet prepared with ionic polymer binder B2) is denoted as C18.

[0243] Comparative Application Example 3

[0244] The lithium iron phosphate positive electrode sheet prepared in Application Example 9 of Patent CN118240508A (lithium iron phosphate positive electrode sheet prepared by ionic polymer binder B2 and PVDF in a mass ratio of 5:5) is recorded as C19.

[0245] Comparative Application Example 4

[0246] The binder solution B3 prepared in Comparative Example 3 was used to prepare an artificial graphite negative electrode sheet for a lithium ion battery. The specific steps are as follows: 188 g of artificial graphite and 6 g of superconducting carbon black were ball-milled at a rotation speed of 1032 rpm for 2 h to obtain a mixed powder; 60 g of the binder solution B2 prepared in Comparative Example 2 and the obtained mixed powder were ball-milled at a rotation speed of 1032 rpm for 4 h, 136 g of pure water (resistivity greater than 0.1 MΩ·cm) was added and the ball-milling was continued for 3 h to obtain a negative electrode slurry; the method of step 4 of Application Example 1 was used for coating and drying to obtain an artificial graphite negative electrode sheet for a lithium ion battery, which was recorded as C20.

[0247] Test Example 1

[0248] The following performance tests were performed on the flexible ionomer binders A1 to A8 prepared in Examples 1 to 8, the binder B1 prepared in Comparative Example 1, and the ionomer binder B2 in Comparative Example 2:

[0249] Viscosity average molecular weight M η Determined according to GB / T 10247-2008 test method;

[0250] The thermal decomposition temperature was measured by a thermogravimetric analyzer (Netzsch, Germany, TG209) from 25 to 600 °C under a nitrogen atmosphere at a heating rate of 10 °C / min;

[0251] The glass transition temperature was measured by differential scanning calorimetry (TADSC Q100) in a nitrogen atmosphere at a temperature range of -80°C to 180°C and a heating / cooling rate of ±10°C / min. The test results of the adhesive properties are shown in Table 1.

[0252] Table 1 Performance indicators of adhesives

[0253] Binder <![CDATA[M η (Yes)]]> <![CDATA[T d (℃)]]> <![CDATA[T g (℃)]]> A1 <![CDATA[5.81×10 4 ]]> 328 -28.8 A2 <![CDATA[5.51×10 4 ]]> 322 -27.6 A3 <![CDATA[5.50×10 4 ]]> 323 -26.6 A4 <![CDATA[4.36×10 4 ]]> 325 -28.2 A5 <![CDATA[4.01×10 4 ]]> 318 -27.4 A6 <![CDATA[5.89×10 4 ]]> 323 -28.5 A7 <![CDATA[4.99×10 4 ]]> 318 -29.8 A8 <![CDATA[2.91×10 4 ]]> 319 -21.7 B1 <![CDATA[5.00×10 5 ]]> 316 -47.0 B2 <![CDATA[5.81×10 4 ]]> 326 5.0

[0254] The flexible ionic polymer binder A1 prepared in Example 1 and the binder B1 prepared in Comparative Example 1 were characterized by using a differential scanning calorimeter. The obtained differential scanning calorimetry curves are as follows: Figure 3 shown.

[0255] It can be seen from Table 1 that the molecular weight of the flexible ionomer binder prepared by the present invention is 2.91×10 4 ~5.89×10 4 Da range, which is much lower than the molecular weight of commercial PVDF. Therefore, it can be expected that under the same conditions, the positive electrode slurry prepared by the binder of the present invention has a lower viscosity and is easier to coat. The thermal decomposition temperature of the flexible ionic polymer binder prepared by the present invention is higher than that of PVDF (316°C). Therefore, the prepared positive electrode sheet has good heat resistance and meets the needs of battery operation under high temperature conditions. From Table 1 and Figure 3 It can be seen that the flexible ionic polymer binder prepared by the present invention has no crystallinity, and its glass transition temperature is in the range of -29.8 to -21.7°C. Although the glass transition temperature is higher than that of PVDF (-47.0°C), since PVDF is a semi-crystalline polymer with a crystalline melting temperature of 160.4°C, crystallization will limit the movement of the polymer chain, making the flexibility of the PVDF binder worse. Although the glass transition of the ionic polymer binder prepared by the present invention is higher, the flexibility of the polymer is good.

[0256] Although the molecular weight and thermal decomposition temperature of the flexible ionic polymer binder prepared by the present invention are similar to those of the ionic polymer binder B2 in Comparative Example 2, the glass transition temperature (-29.8 to -21.7°C) of the flexible ionic polymer binder prepared by the present invention is much lower than the glass transition temperature (5.0°C) of B2. Therefore, the flexible ionic polymer binder prepared by the present invention has better flexibility.

[0257] Test Example 2

[0258] The surface density of the active material of the lithium iron phosphate pole pieces C1 to C19 of the lithium ion battery is the mass of lithium iron phosphate per unit area, which is obtained by calculation; the peel strength between the dry slurry coating on the surface of the current collector in the pole piece and the current collector is determined according to the test method of GB / T 2791-1995; the surface density and peel strength of the lithium iron phosphate pole piece obtained by the test are shown in Table 2.

[0259] The method of assembling a lithium iron phosphate|metal lithium battery using the prepared lithium iron phosphate pole pieces C1-C19 as the positive electrode of the lithium ion battery and lithium metal as the negative electrode of the battery is as follows:

[0260] Lithium hexafluorophosphate (LiPF6) is dissolved in a solution of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1 as the electrolyte (wherein the concentration of LiPF6 is 1 mol / L); a polypropylene microporous membrane (Celgard 2325) is used as a diaphragm; the prepared C1-C19 lithium iron phosphate electrode is the positive electrode of the battery, and lithium metal is the negative electrode of the battery. The stainless steel gasket, lithium metal, electrolyte, diaphragm, electrolyte, lithium iron phosphate positive electrode, stainless steel gasket and stainless steel spring are placed in the center of the CR2032 negative electrode shell in the order, and the CR2032 positive electrode shell is placed on the top. Then the battery is placed in the MSK 110 battery packaging machine, and the pressure is increased to 50psi in the locked state to package, and the lithium iron phosphate|metal lithium battery is obtained after unlocking. The amount of electrolyte in each lithium iron phosphate|metal lithium battery is 40μL, and an equal amount is required to be dripped on both sides of the diaphragm to fully wet the diaphragm. The battery assembled with C1~C19 lithium iron phosphate pole pieces is a lithium iron phosphate|metal lithium battery, which is denoted as D1~D19 respectively.

[0261] The cyclic voltammetry (CV) curve of lithium iron phosphate|metal lithium battery was tested by an electrochemical workstation (VersaSTAT 3, USA) with a voltage range of 2.0-4.5V and a scan rate of 0.1-0.8mV / s. The relationship between the peak current and the square root of various scan rates can be obtained from the cyclic voltammetry curves at different scan rates. The diffusion coefficient of lithium ions (D Li +).

[0262]

[0263] Among them I P is the peak current (A); v is the scan rate (V s- 1 ); n is the number of transferred electrons; A is the electrode area (cm 2 ); r$r,i + is the lithium ion diffusion coefficient (cm 2 s- 1 ); is the volume concentration of lithium ions in the electrode (mol cm- 3 ). DAi3 can be based on I P and The slope of the linear relationship between them is calculated.

[0264] The cyclic voltammetry curves of lithium iron phosphate|metal lithium batteries D1 and D17 were tested using a voltammetry curve tester at 25°C, different scan rates (0.1-0.8 mV / s), and a voltage range of 2.0-4.5 V. The results are as follows: Figure 4 and Figure 5 As shown. Figure 4 and Figure 5 It can be seen that the lithium iron phosphate|metal lithium battery assembled with the lithium iron phosphate positive electrode sheet prepared by the flexible ionic polymer binder of the present invention has a better cycle performance

[0265] The relationship between the peak current and the square root of various scan rates obtained from the cyclic voltammetry curves of lithium iron phosphate|metal lithium batteries D1 and D17 at different scan rates was calculated. The results are as follows Figure 6 As shown. Figure 6 It can be seen that the lithium iron phosphate positive electrode sheet prepared by using the flexible ionic polymer binder provided by the present invention has a higher lithium ion diffusion coefficient and has good cycle performance.

[0266] The long cycle charge and discharge curve of lithium iron phosphate|metal lithium battery D1 was tested by battery cycle tester at 25℃, cut-off voltage of 2.5~4.2V and rate of 0.5C. The results are as follows Figure 7 shown.

[0267] The battery cycle tester was used to test the charge and discharge curves of lithium iron phosphate|metal lithium battery D1 at 25°C, cut-off voltage of 2.5-4.2V, and at 0.05C, 0.1C, 0.2C, 0.3C, and 0.5C rates. The results are as follows Figure 8 shown.

[0268] from Figure 7 and Figure 8 It can be seen that the lithium iron phosphate|metal lithium battery assembled with the lithium iron phosphate positive electrode sheet prepared by the flexible ionic polymer binder provided by the present invention has a higher initial discharge specific capacity, and also has a higher discharge specific capacity and capacity retention rate after cycling 500 times at a current density of 0.5C.

[0269] The battery specific capacity refers to the initial discharge specific capacity and the 500th cycle discharge specific capacity of the assembled lithium iron phosphate|metal lithium battery at a current density of 0.5C. The test instrument is a battery cycle tester (Wuhan Blue Electric, CT3002A), the cut-off voltage is 2.5~4.2V, the test temperature is 25°C, and the theoretical specific capacity of the positive electrode active material is 170mAh / g. The results of the initial discharge specific capacity, the 500th cycle discharge specific capacity and the retention rate (ratio of discharge specific capacity to initial discharge specific capacity) of the lithium iron phosphate|metal lithium battery obtained by the test are shown in Table 2.

[0270] Table 2 Performance indicators of lithium iron phosphate | lithium metal batteries

[0271]

[0272] As can be seen from Table 2, under the condition of similar lithium iron phosphate surface density, the lithium iron phosphate positive electrode sheets (C1-C16) prepared by the flexible ionic polymer binder of the present invention, whether used alone or mixed with PVDF, have higher peel strength and higher lithium ion diffusion coefficient than the lithium iron phosphate positive electrode sheets (C17) prepared using only PVDF binder, and the assembled battery has higher initial discharge specific capacity and capacity retention rate. Compared with the lithium iron phosphate positive electrode sheets (C18-C19) prepared by the binder reported in patent CN118240508A, the lithium iron phosphate positive electrode sheets (C1-C16) prepared by the present invention have similar peel strength, but higher lithium ion diffusion coefficient, and the assembled battery has higher initial specific capacity and capacity retention rate.

[0273] Test Example 2

[0274] Characterization of lithium iron phosphate | artificial graphite full battery parameters: The lithium iron phosphate positive electrode C1 provided in Application Example 1, the lithium iron phosphate positive electrode C9 provided in Application Example 9, the lithium iron phosphate positive electrode C17 provided in Comparative Application Example 1 and the lithium iron phosphate positive electrode C18 provided in Comparative Application Example 2 are used as positive electrode sheets, and the artificial graphite negative electrode C20 provided in Comparative Application Example 4 is used as negative electrode sheet to assemble lithium iron phosphate | artificial graphite full batteries, which are named E1 to E4 respectively.

[0275] The method of assembling lithium iron phosphate | artificial graphite battery is as follows:

[0276] Lithium hexafluorophosphate (LiPF6) is dissolved in a solution of ethylene carbonate (EC), dimethyl carbonate (DMC) and ethyl methyl carbonate (EMC) in a volume ratio of 1:1:1 as the electrolyte (wherein the concentration of LiPF6 is 1 mol / L); a polypropylene microporous membrane (Celgard 2325) is used as a diaphragm; C1, C9, C17 or C18 is used as a positive electrode; and an artificial graphite electrode is used as a negative electrode. The stainless steel gasket, artificial graphite negative electrode, electrolyte, diaphragm, electrolyte, lithium iron phosphate positive electrode, stainless steel gasket and stainless steel spring are placed in the center of the CR2032 negative electrode shell in the order of stainless steel gasket, artificial graphite negative electrode, electrolyte, diaphragm, electrolyte, lithium iron phosphate positive electrode, stainless steel gasket and stainless steel spring. The CR2032 positive electrode shell is placed on the top, and then the whole is placed in the MSK 110 battery packaging machine. The pressure is increased to 50psi in the locked state to package, and the lithium iron phosphate|artificial graphite batteries E1 to E4 are obtained after unlocking. The amount of electrolyte used in each lithium iron phosphate | artificial graphite battery is 40μL, and an equal amount is required to be dropped on both sides of the diaphragm to ensure sufficient infiltration of the diaphragm.

[0277] The assembled E1-E5 lithium iron phosphate|artificial graphite full batteries were subjected to battery cycle testing in a battery cycle tester (Wuhan Blue Electric, CT3002A), wherein the cut-off voltage was 2.5-4.2V, the test temperature was 25°C, the rate was 0.5C, and the standard specific capacity of the positive electrode active material was 170mAh / g. The results of the test for the initial specific capacity of the battery cycle, the 800th cycle discharge specific capacity, and the capacity retention rate (the ratio of the discharge specific capacity to the initial discharge specific capacity) are shown in Table 3.

[0278] Table 3 Performance indicators of lithium iron phosphate | artificial graphite battery

[0279]

[0280] The full battery performance results in Table 3 further show that the lithium iron phosphate|artificial graphite battery assembled with the lithium iron phosphate positive electrode sheets prepared by the flexible ionic polymer binder of the present invention, whether used alone or mixed with PVDF, has higher initial discharge specific capacity and capacity retention rate than the lithium iron phosphate|artificial graphite battery assembled with the lithium iron phosphate positive electrode sheets prepared using only the PVDF binder.

[0281] In summary, when the flexible ionic polymer binder provided by the present invention is used to prepare positive electrode sheets of lithium ion batteries, the discharge specific capacity and cycle stability of lithium ion batteries assembled with the positive electrode sheets prepared by the binder can be significantly improved.

[0282] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A flexible ionic polymer binder having a chemical structure as shown in Formula I: In the formula I, R1, R6 and R7 are independently hydrogen or alkyl; R2 is alkylene or aralkylene; R3 and R4 are independently alkyl or aralkyl; R5 and R8 are independently alkyl; X is BF4, 1 / 2[SO4], 1 / 2[CO3], CH3SO3, CF3SO3 or (CF3SO2)2N; m=4~40;x+y+z=1, wherein x>0, y≥0, z≥0.

2. The flexible ionomer binder according to claim 1, characterized in that: In the formula I, R1, R6 and R7 are all hydrogen; R2 is an alkylene group; R3, R4, R5 and R8 are all alkyl groups; X is BF4, 1 / 2[SO4], or (CF3SO2)2N; m=4-40; x+y+z=1, wherein 0<x<0.7, 0≤y≤0.4, 0≤z≤0.

4.

3. The flexible ionomer binder according to claim 1 or 2, characterized in that: Has the chemical structure shown below:

4. The method for preparing the flexible ionomer binder according to any one of claims 1 to 3, comprising: The first ester monomer is sequentially subjected to a first free radical polymerization, a first quaternization and a first anion replacement to obtain a flexible ionic polymer binder; the first ester monomer is dialkylamino acrylate, or a combination of one or both of polyethylene glycol acrylate and acrylate and dialkylamino acrylate; Alternatively, the second ester monomer is subjected to a second free radical polymerization to obtain a flexible ionic polymer binder; the second ester monomer is a trialkylamino acrylate anion salt, or a combination of one or two of polyethylene glycol acrylate and acrylate and a trialkylamino acrylate anion salt; the trialkylamino acrylate anion salt is obtained by sequentially subjecting dialkylamino acrylate to a second quaternization and a second anion replacement.

5. The preparation method according to claim 4, characterized in that: The following steps are involved: (1) mixing a first ester monomer, a first initiator and a first solvent to perform a first free radical polymerization reaction to obtain a first polymer solution; (2) mixing the first polymer solution obtained in step (1) with a first alkylating agent and a second solvent to perform a first quaternization reaction to obtain a second polymer solution; (3) The second polymer solution obtained in step (2) is mixed with the first anion salt and the third solvent to perform a first anion replacement reaction to obtain a flexible ionic polymer binder.

6. The preparation method according to claim 4, characterized in that: The following steps are involved: 1) mixing dialkylamino acrylate, a second alkylating agent and a fourth solvent, and performing a second quaternization reaction to obtain a trialkylamino acrylate salt solution; 2) mixing the acrylate trialkylamino ester salt solution obtained in step 1) with the second anion salt and the fifth solvent, and performing a second anion replacement reaction to obtain acrylate trialkylamino ester anion salt; 3) Mixing the second ester monomer of the trialkylamino acrylate anion salt obtained in step 2), a second initiator and a sixth solvent, and performing a second free radical polymerization reaction to obtain a flexible ionic polymer binder.

7. Use of the flexible ionic polymer binder according to any one of claims 1 to 3 or the flexible ionic polymer binder prepared by the preparation method according to any one of claims 4 to 6 in positive electrode sheets of lithium ion batteries.

8. A positive electrode plate for a lithium-ion battery, comprising a current collector and a positive electrode material coated on the surface of the current collector; the positive electrode material comprises a positive electrode active material, a binder and a conductive agent, characterized in that: The binder includes the flexible ionic polymer binder according to any one of claims 1 to 3 or the flexible ionic polymer binder prepared by the preparation method according to any one of claims 4 to 6.

9. The positive electrode sheet of a lithium-ion battery according to claim 8, characterized in that: The binder also includes polyvinylidene fluoride, and the mass ratio of the flexible ionomer binder to polyvinylidene fluoride is 1:(0-5).

10. The positive electrode sheet of a lithium-ion battery according to claim 8 or 9, characterized in that: The mass ratio of the positive electrode active material to the binder is (60-98):(1-20).

Citation Information

Patent Citations

  • Single-component polyion liquid adhesive as well as preparation method and application thereof

    CN115353837A

  • Terpolymer adhesive tape type dry and wet dual-purpose adhesive as well as preparation method and application thereof

    CN116333654A

  • Ionic polymer binder as well as preparation method and application thereof

    CN118240508A

  • Ionic polymer binder based on viologen as well as preparation method and application of ionic polymer binder

    CN118703137A

  • Polymer electrolyte, and its manufacturing method

    JP2007280912A

Cited By

  • Binder, negative electrode slurry, negative electrode plate and battery

    CN120442187A

  • Ionic block copolymer as well as preparation method and application thereof

    CN121005846A